Different Temperature and UV Patterns Modulate Berry Maturation and Volatile Compounds Accumulation in Vitis sp. - Campos-Arguedas, Francisco; Sarrailhé, Guillaume; Nicolle, Paméla; Dorais, Martine; Brereton, Nicholas J. B.; Pitre, Frederic E.; Pedneault, Karine (Frontiers in Plant Science, 2022)
Recent rises due to Global Warming have been reshaping the dynamic of harvest and wine production worldwide by globally increasing seasonal heat accumulation. However, grapevines also experience larger temperature ranges throughout the growing season, and new temperature patterns currently emerge, with potential impacts on plant growth, phenology, and metabolism. As grapevine berry growth occurs through two main phases (development; Pre-veraison, and ripening; Post-veraison), each relating to specific metabolic events, we hypothesized that such differences in patterns of growing-degree days accumulation may affect berry ripening and composition at harvest. To test this hypothesis, we triggered moderate temperature increases of grapevine plants at different times during berry growth, using mini-greenhouses installed on rows during Pre-veraison (inflorescence to beginning of berry softening), Post-veraison (berry softening to full maturity) and Whole season (inflorescence to full maturity), along with a control. The experiment was conducted on Vitis sp. L’Acadie blanc, in Nova Scotia, Canada. Mature berries were sampled at three phenological stages (EL-36, EL-37 and EL-38), using liquid nitrogen. Free and bound volatile compounds were extracted by SPE and analyzed by GC-MS. Berries from grapevine exposed to higher temperatures during early berry growth (Pre-veraison, Whole season) showed a greener color and accumulated higher concentrations of benzene derivatives (2-phenylethanol, benzyl alcohol) when compared to the control. In contrast, Control grapevine produced darker berries, with higher levels of hydroxy-methoxy-substituted volatile phenols, terpenes and C13-norisoprenoids. These results suggests that early temperature increase modulated the phenylpropanoid pathway and negatively affected the mevalonate pathway in developing berries. More interestingly, these effects were durable in time as they affected berry composition at harvest. This study provides insights about the relationships between abiotic conditions during berry development and ripening, and secondary metabolism in grapevine. It also highlights the significance of first developmental stages on berry quality at harvest.